The nationalization of Hindu traditions : Bhāratendu Hariśchandra and nineteenth-century Banaras - Dalmia, Vasudha (Oxford University Press, 1997)
Cultural biography of Bhāratendu Hariścandra, 1850-1885, major Hindi writer of the nineteenth century.